Kodeks etyczny samorządu zawodowego. Gwarancja bezpieczeństwa czy pułapka łatwowierności? - Rotengruber, Przemysław (Annales. Etyka w Życiu Gospodarczym, 2015)
Representatives of business ethics examine the economic challenges of our time. They believe that in the use of ethics they are able to keep under control this sphere of human activity. Alas, this attempt meets the following obstacle. This ethical claim does not work as an objective criterion for measuring good vs evil as long as it is not supported by epistemological evidence (on its validity). Therefore business ethicists focus their attention on the codes of ethics which they see as the expected solution to the problem. A code of ethics is drawn up by an economic organisation which – in this way – declares its acceptance. Meanwhile, this declaration leads to the question of how to sift the ethical guarantees from empty promises? Can the social addressee of an ethical code trust its author? This doubt relates in particular to professional associations. Having a legal prerogative they are expected to recognize their fiduciary duty of loyalty to their social interlocutor. When they do not want to meet these obligations, they may use a code of ethics as a tool of manipulation. Under those circumstances, the code is something opposite to what is expected.